Pengaruh Kompetensi Terhadap Kinerja Pegawai Pada Dinas â€œXâ€Kabupaten Bengkalis - Rahmat, Yogie (Eko dan Bisnis: Riau Economic and Business Review, 2023)
Performance is the result or level of success of an individual in carrying out tasks compared to various possibilities, such as work standards, targets, or predetermined and mutually agreed criteria. The objective of this research is to determine the Influence of Competence on Employee Performance in the "â€œXâ€" District Office of Bengkalis Regency. In this study, a sample of 84 respondents was used. The result of the regression equation Y = 19.705 + 0.688x indicates that the value of a = 19.705 suggests that if Competence is considered zero, the level of Performance is 19.705 units. The regression coefficient value = 0.688 indicates that if the Competence value increases by 1 unit, the Performance variable will increase by 0.688 units. The positive regression coefficient means that the better the Competence, the higher the Employee Performance in the "â€œXâ€" District Office of Bengkalis Regency will be. From the t-test results, the t-value for the Competence variable is 8.946 (greater than the t-table value of 1.989), and the P-value is 0.000 < 0.05. Therefore, this research shows that Competence significantly influences Employee Performance in the "â€œXâ€" District Office of Bengkalis Regency. Based on the correlation coefficient (R) value of 0.703, it means that there is a strong relationship between the Competence variable and Performance. Then, the coefficient of determination R Square is 0.494, indicating that the Competence variable contributes 49.4% to Employee Performance in the "â€œXâ€" District Office of Bengkalis Regency, while the remaining 50.6% is influenced by factors not examined in this research.